The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.12688/f1000research.16433.1
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for diphtheria outbreak in children aged 1-10 years in East Kalimantan Province, Indonesia

Abstract: Background: Diphtheria remains a health problem, especially in developing countries. In November 2017, the Indonesian Ministry of Health stated that there was a diphtheria outbreak in Indonesia. East Kalimantan is one of the provinces that experienced this disease outbreak. This study analyzes the risk factors for diphtheria outbreak in children aged 1-10 years. Methods: A case-control study was conducted on 37 respondents. Research variables consist of immunization status against diphtheria, pertussis and tet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 17 publications
(17 reference statements)
1
7
1
Order By: Relevance
“…We found no association between carrier status and bed-sharing, staying at the school dormitory, or less frequent bathing, but several other studies have identified those as risk factors for infection (17)(18)(19)(20)(21). A small number of carriers might be a reason that we could not identify the association; biologic characteristics, such as age or individual immunity level, might have been played a greater role than social factors.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…We found no association between carrier status and bed-sharing, staying at the school dormitory, or less frequent bathing, but several other studies have identified those as risk factors for infection (17)(18)(19)(20)(21). A small number of carriers might be a reason that we could not identify the association; biologic characteristics, such as age or individual immunity level, might have been played a greater role than social factors.…”
Section: Discussioncontrasting
confidence: 72%
“…The survey teams interviewed each participant by using a standardized questionnaire and collected sociodemographic information. Based on previously reported risk factors for diphtheria infection or carriage of C. diphtheriae, age, vaccination history, seropositivity (diphtheria toxoid IgG titer >0.1 IU/mL), bed-sharing, school attendance, staying in school dormitories, household size, frequency of bathing or handwashing, having livestock or companion animals, diphtheria toxoid IgG level, and mid-upper arm circumference (MUAC) were assessed for their association with carriage of Corynebacterium species (13,(17)(18)(19)(20)(21). MUAC was used as a measure of the nutritional status of children 1-5 years of age.…”
Section: Data and Sample Collection And Ethicsmentioning
confidence: 99%
“…The first case in 2016 was also the first case appeared in the Jatiluhur Health Center until it spread to the village of Cisalada, Jatiluhur sub-district. The previous research in Indonesia showed that child/parent mobility was the major risk factor of diphtheria Epidemiology and Society Health Review| ESHR outbreak (14). Other risk factors of diphtheria occurrence were nutritional status of children and the source of transmission (15).…”
Section: Discussionmentioning
confidence: 99%
“…Investigation is related to how chronologically the case occurs, confirms the diagnosis, looks for additional cases, and makes sure there is an outbreak. In the case of diphtheria, epidemiological investigations aim to determine the risk factors for diphtheria so that the spread of diphtheria can be stopped immediately (Widoyono, 2008;Ramdan et al, 2018).…”
Section: Discussionmentioning
confidence: 99%